2019
DOI: 10.3390/ijerph16091485
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Harsh Physical Parenting and Behavioral Problems in Children in Religious Families in Yemen

Abstract: The present study examined maternal religiosity as an underlying cultural factor in the effect of harsh physical parenting on child behavioral problems. Data was collected via a discipline observational task, religiosity-based vignettes, and a questionnaire in a group of 62 mothers and their children in slum areas in Yemen. Moderation and mediation models were tested, where the role of maternal religiosity as a predictor and a moderator in the association between harsh physical parenting and child behavioral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Maternal physical punishment of first generation Chinese American mothers of 3-to-5-year-old children was significantly associated with more externalized behaviors 6 months later, at high levels of maternal acculturation and at low levels of child inhibitory control (Yu et al, 2018). In low-income Muslim families in Yemen, high levels of physically harsh maternal parenting was associated with increased externalized and internalized behavior problems in children, only when mothers had medium or high levels of religiosity (Alsarhi et al, 2019). Moreover, children’s behaviors were examined using mediation models that included maternal corporal punishment as the mediator variable .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal physical punishment of first generation Chinese American mothers of 3-to-5-year-old children was significantly associated with more externalized behaviors 6 months later, at high levels of maternal acculturation and at low levels of child inhibitory control (Yu et al, 2018). In low-income Muslim families in Yemen, high levels of physically harsh maternal parenting was associated with increased externalized and internalized behavior problems in children, only when mothers had medium or high levels of religiosity (Alsarhi et al, 2019). Moreover, children’s behaviors were examined using mediation models that included maternal corporal punishment as the mediator variable .…”
Section: Resultsmentioning
confidence: 99%
“…There were also significant relationships between maternal corporal punishment and concurrent internalized problems in children (Berthelon et al, 2020; Bevilacqua et al, 2021; Wolford et al, 2019). Corporal punishment was moderated by low levels of inhibitory control in children (Yu et al, 2018), high levels of maternal acculturation in the first generation Chinese American mothers (Yu et al, 2018) and medium or high levels of maternal religiosity (specifically in Muslim families from Yemen) (Alsarhi et al, 2019). Maternal corporal punishment mediated the association between living in disordered neighborhoods (Pei et al, 2019), negative neighborhood environments and maternal stress (Pei et al, 2019), intimate partner violence, psychological aggression (Grasso et al, 2016), and externalized problems in children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conceptualized the belief in divine punishment as a distinct dimension of religiosity, but did not focus on its associations with parenting. This belief was associated with a generalized authority orientation, obedience orientation in parenting, and a lack of tolerance (Alsarhi et al, 2019; Dumas & Nissley-Tsiopinis, 2006; Duriez et al, 2009; Johnson et al, 2015; Mahoney et al, 2008; Murray-Swank et al, 2006). Thus, the role of the belief in divine punishment in predicting parenting behaviors that are known to be associated with negative outcomes in children merits an emphasis on this dimension of religious belief, alongside other dimensions that include beliefs in the existence and benevolence of the divine and participation in religious rituals.…”
Section: Sociocultural Background Of the Present Studymentioning
confidence: 99%
“…One study that examined mothers' religiosity as a major cultural factor in the impact of harsh physical parenting on the behavioral problems of children showed that there was no direct correlation between harsh physical parenting and maternal religiosity and children's behavioral issues. However, it was found that the positive association between harsh physical parenting and children's behavior problems is stronger when parents are more religious (Alsarhi, Prevoo et al, 2019). A study done on female genital cutting (FGC) behavior in four governorates discovered that FGC was prevalent in 48% mothers, while daughters' FGC was 34%.…”
Section: Family and Social Studiesmentioning
confidence: 99%